Percepção da manobra de versão fetal externa pela grávida - Garcia,Mafalda (2021)
Abstract Overview and aims: External cephalic version (ECV) is a maneuver that can diminish the cesarean section rate. The objective of our study was to assess women’s perception with ECV to improve counselling and its implementation. Study Design: Semi structured interviews with closed and open questions were conducted by phone. Population: Women subjected to ECV between January 2015 and August 2018. Methods: Women’s answers descriptive analysis. Results: Sixty six women answered the questionnaire. Pain was reported as intense by 48,5% and severe by 12,1%. The majority considered ECV as an alternative to cesarean section and 22,7% had tried other techniques before ECV. Twenty four women felt anxious before ECV but only 15,1% regretted their decision to undergo ECV. More than 60% would consider this maneuver in a subsequent pregnancy or recommend it to a friend. There was no association between the referred pain and the success of ECV. Conclusion: ECV is perceived as painful by most women and causes anxiety to a significant number of patients. Therefore, ECV must be attempted by experienced practitioners with careful attention to maternal mood.